A sustainable hybrid manufacturing/remanufacturing system with two-way substitution and WEEE directive under different market conditions. (2nd November 2022) - Khakbaz, Amir; Tirkolaee, Erfan Babaee
Abstract : In recent years, environmental regulations, public awareness and economic opportunities have motivated many researchers to study Hybrid Manufacturing/Remanufacturing Systems (HMRSs). This research addresses the production planning of a sustainable hybrid production system including integrated manufacturing and remanufacturing processes within a closed-loop reverse logistics network with two-way substitution and Waste Electrical and Electronic Equipment (WEEE) directive. One of the main options of our developed model is that a number of customers may switch from new products to remanufactured ones and vice versa. Moreover, a stochastic demand is met by purchasing manufactured and remanufactured products in primary and secondary markets, respectively. Six scenarios are considered based on the capacity of manufacturing and remanufacturing processes to develop a sustainable manufacturing/remanufacturing policy that would maximize the expected profit. Through sensitivity analyses, the impacts of the key parameters such as substitution rates, sales price, yield rate and production costs are investigated to provide useful managerial insights. Based on the obtained results, with the increase of substitution rates, the expected profit and the recycling rate increase. Furthermore, with the increase in production costs, the expected profit and the recycling rate decrease.